Patients' experiences of being treated for acute illness at home as an alternative to hospital admission: a qualitative study in Denmark. Issue 5 (24th May 2022) - Bove, Dorthe Gaby; Christensen, Pernille Edelgaard; Gjersøe, Peter; Lavesen, Marie
Abstract : Objective: We aimed to investigate the experiences of Danish patients treated at home for an acute illness instead of being hospitalised. Design: This study had a qualitative design inspired by the methodology of interpretive description. Data were collected through semistructured interviews. Setting: Home treatment was conducted by a team of nurses (n=10–15) supported by physiotherapists and physicians, all affiliated with an emergency department, located in the capital region of Denmark. Interviews were conducted between August 2020 and April 2021. Participants: Twenty-one patients, aged 34–94 years, narrated their experiences of being treated at home for an acute illness. Results: The overarching theme in our analyses was that 'being the centre of the nurses' attention provided safety, patient involvement and quality of life during home treatment'. The following six themes emerged from analyses: (1) exclusive attention facilitates involvement and activity; (2) hospitals are for the sick; (3) maintaining a meaningful everyday life; (4) the hospital exudes productivity and busyness; (5) family relations and roles are maintained; (6) and concerns of deterioration. Conclusions: From a patient's perspective, home treatment made sense and was perceived as a quality improvement. Being the centre of nurses' attention induced a sense of safety, involvement and enhanced quality of life among patients during the treatment course for an acute illness.